Analisis Word of Mouth Di Kalangan Konsumen Terhadap Pembelian Produk Mie Gaga - Kharimah, Septiana Nurul; Erwin Permana (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
Word Of Mouth (WoM) marketing is considered the most effective marketing strategy. This study analyzes WoM among consumers regarding the purchase of Mie Gaga products. The research method used is descriptive qualitative. Data were obtained through searching and observing in digital bases and official publications. The results indicate that WoM among consumers regarding the purchase of Mie Gaga focuses on consumer satisfaction and outstanding products such as Gaga 100 Extra Spicy Jalapeno, building a positive brand image. Strong consumer support is a key factor in creating positive WoM. Product and service adaptation, as well as building strong relationships through personal interaction and relevant incentives, can enhance positive WoM. The use of social media, especially TikTok, strengthens positive WoM. Creative and relevant content can attract consumer attention and strengthen the brand image. Mie Gaga can utilize social media to expand their WoM and popularity amidst the instant noodle industry competition. Increased brand awareness among consumers can trigger changes in purchasing behavior, such as switching to Mie Gaga, indicating a strong WoM. This analysis highlights the importance of product and service quality and responsiveness to consumer reviews to avoid negative WoM. By maintaining quality and strengthening consumer relationships, Mie Gaga builds positive WoM, enhances consumer loyalty, and expands market share in the instant noodle industry through storytelling and Key Opinion Leaders.